A revision of the genus Yoshiakioclytus Niisato, 2007 (Coleoptera: Cerambycidae: Cerambycinae: Anaglyptini) - Huang, Gui-Qiang; Chen, Li (Zootaxa, 2016)
A taxonomic revision of the genus Yoshiakioclytus Niisato is presented. A new species, Y. qiaoi sp. nov., is described from North China. Three new combinations, Y. ruficaudus (Gressitt, 1951) comb. nov., Y. breuningi (Tippmann, 1955) comb. nov. and Y. stigmosus (Holzschuh, 2003) comb. nov., are proposed. The male of Y. breuningi (Tippmann, 1955) is redescribed, male terminalia of Y. breuningi is described for the first time. Yoshiakioclytus is redescribed and a key to Yoshiakioclytus species is presented.